KEPUASAN MASYARAKAT KECAMATAN KABANDUNGAN TERHADAP PELAYANAN PENYALURAN BANTUAN LANGSUNG TUNAI DANA DESA DI MASA PANDEMIC COVID-19 - Dede Citrawati; Rita Rahmawati; Euis Salbiah (LPPM Universitas Djuanda Bogor, 2022)
The Covid-19 pandemic has greatly impacted the community, especially in the economic sector which greatly affects their welfare. In this case, the government makes efforts by holding a Village Fund Direct Cash Assistance program sourced from the Village Fund. In the service process for distributing direct cash assistance from village funds, several problems were found including: the timing of the distribution of social assistance was not on time, there was a collection of fees, the service time was short and there was no media for complaints about the service process for distributing direct cash assistance from village funds. The purpose of this study was to determine how the quality of service, community satisfaction and to determine the effect of service quality in the distribution of direct cash assistance from village funds on the satisfaction of the people of the Kabandungan sub-district. The research method used in this research is associative research method using a quantitative approach. Data collection techniques include: library data, observation, interviews and questionnaires. And the data analysis technique used is the Weigh Mean Score (WMS) and the Spearman Rank test. The results of this study show that of the 139 respondents for the service quality variable (X) of 4.46 which is in the very good criteria and the variable of community satisfaction (Y). ) of 4.28 which is in the very good criteria. Furthermore, for the results of the associative test with the Spearman Rank test, it gets a value of 0.603, which means that there is a relationship between the service quality variable (X) on community satisfaction (Y) with the strength of the relationship, namely Strong. With a significance value of 0.000 or less than 0.05 which indicates there is a significant relationship and the direction of the relationship is positive. The results of the calculation of the coefficient of determination found a value of 36.3609%, this value indicates that service quality contributes or influences community satisfaction. while the remaining 63,6391% is influenced by other factors.